2020
DOI: 10.1038/s41467-020-14676-4
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota mediates intermittent-fasting alleviation of diabetes-induced cognitive impairment

Abstract: Cognitive decline is one of the complications of type 2 diabetes (T2D). Intermittent fasting (IF) is a promising dietary intervention for alleviating T2D symptoms, but its protective effect on diabetes-driven cognitive dysfunction remains elusive. Here, we find that a 28-day IF regimen for diabetic mice improves behavioral impairment via a microbiota-metabolites-brain axis: IF enhances mitochondrial biogenesis and energy metabolism gene expression in hippocampus, restructures the gut microbiota, and improves m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
340
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 332 publications
(380 citation statements)
references
References 66 publications
14
340
0
1
Order By: Relevance
“…We also found that increased Enterococcaceae were part of the small cluster of taxa that corelated with impaired insulin secretion. This result is consistent changes in Enterococcaceae regulating insulin, since intermittent fasting lowers blood insulin and glucose and improved insulin sensitivity, coincident with a decreased relative abundance of Enterococcaceae in obese, diabetic, db/db mice [21]. Furthermore, while bacterial LPS has been shown to impair insulin clearance, we have recently shown that members of the Enterococcaceae family compartmentalize in the tissues of individuals with T2D, independently of obesity [22].…”
Section: Discussionsupporting
confidence: 78%
“…We also found that increased Enterococcaceae were part of the small cluster of taxa that corelated with impaired insulin secretion. This result is consistent changes in Enterococcaceae regulating insulin, since intermittent fasting lowers blood insulin and glucose and improved insulin sensitivity, coincident with a decreased relative abundance of Enterococcaceae in obese, diabetic, db/db mice [21]. Furthermore, while bacterial LPS has been shown to impair insulin clearance, we have recently shown that members of the Enterococcaceae family compartmentalize in the tissues of individuals with T2D, independently of obesity [22].…”
Section: Discussionsupporting
confidence: 78%
“…Calorie restriction (CR) has been well documented to mitigate obesity-related metabolic diseases and enhance cognitive performance, promote hippocampal neurogenesis, and regulate clock genes. [17][18][19][20] Methionine (Met), a sulfur-containing amino acid, participates in energy-metabolism homeostasis by acting through several nutritional-response signaling pathways. [21] Notably, Met restriction (MR) represents an improved strategy that produces beneficial effects similar to those induced by CR without the reduction in caloric intake.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes-induced brain injury manifests as neurodegeneration, cerebral infarction, and progressive cognitive decline. [5][6][7] Evidence arising from diabetic animal models indicates that neuronal death is one of the major factors causing brain injury. 8,9 However, the underlying molecular mechanism of neuronal death in DM is still unclear.…”
Section: Introductionmentioning
confidence: 99%